BANDOTAN LEAF EXTRACT THERAPY ON IL 6 PROFILE IN WISTAR RATS WITH TYPE 2 DIABETES MELLITUS - Putri Kurniasiwi; Hilari Rio Rosa Nastiti; Mochamad Rizal Maulana (Nursing Sciences Journal, 2026)
Diabetes Mellitus (DM) is a non-communicable disease that has become a serious public health problem in Indonesia and the world. Indonesia ranks 7th in the world with 10.7 million diabetes sufferers in 2019 and this number is expected to increase to 13.7 million in 2030 and 16.6 million in 2045. Complications that occur in DM sufferers are due to cell damage and death caused by increased oxidative stress and the activity of inflammatory mediators including interleukin-6 (Il-6). Administration of oral hypoglycemic drugs to DM patients does not show improvement in oxidative stress. Additional therapy is needed for DM patients that can reduce oxidative stress and inflammatory mediators and support the work of endogenous antioxidants. Bandotan leaves are plants that contain antioxidants and are used as a traditional medicine for DM patients. The purpose of this study was to determine the profile of Il-6 as a marker of inflammation due to oxidative stress in DM patients after administration of bandotan leaf extract. The research revealed significant differences between the control, bandotan, and glimberclamide groups. The bandotan group had the lowest IL-6 levels at 1.63 pg/ml. Bandotan leaf extract caused the least inflammation compared to the control and glimberclamide groups.